Promoting ecoliteracy: the challenges of children's literature in the new millennium - Ramos, Rui (2013)
Bringing together theoretico-methodological principles of Linguistics and studies on Children’s Literature, this chapter aims to analyse a corpus of picturebooks published in Portugal in the last decade in order to identify the main innovations used to portray nature and the environment, and to reflect upon the challenges facing contemporary Portuguese Children’s Literature.